2015
DOI: 10.1097/dbp.0000000000000224
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Difficulties are Associated with Parent Report of Sluggish Cognitive Tempo

Abstract: Objective Sleep disturbance is considered both a behavioral symptom of and a contributor to functional difficulties in children with attention-deficit/hyperactivity disorder (ADHD). The construct of sluggish cognitive tempo (SCT) has also been linked to ADHD; however, little is known regarding the effects of sleep specifically on SCT symptoms. This study examined the association between parent-reported sleep disturbance and parent- and teacher-reported SCT, while controlling for the effects of ADHD and mood sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 28 publications
2
16
0
1
Order By: Relevance
“…Interestingly, DAS-II Pattern Construction and Copying and NEPSY Visual Attention scores have been shown to be lower in individuals with sleep-disordered breathing than typically developing controls and associated with a Total Arousal Index (a score derived from sleep time combining respiratory and spontaneous arousal) (O'Brien et al, 2004); SCT symptoms have also been shown to be associated with sleep difficulties (Becker, Garner, & Byars, 2016; Koriakin, Mahone, & Jacobson, 2015). The DAS-II Pattern Construction and Copying, and NEPSY Visual Attention tasks also involve motor speed and one previous study did find evidence for slower motor speed in girls with ADHD who also had high SCT (Hinshaw et al, 2002); the current study also showed higher teacher rated SCT symptoms predicted slower simple reaction times in the computerized Bubbles task, and poorer inhibition on the Animal Go/NoGo task.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, DAS-II Pattern Construction and Copying and NEPSY Visual Attention scores have been shown to be lower in individuals with sleep-disordered breathing than typically developing controls and associated with a Total Arousal Index (a score derived from sleep time combining respiratory and spontaneous arousal) (O'Brien et al, 2004); SCT symptoms have also been shown to be associated with sleep difficulties (Becker, Garner, & Byars, 2016; Koriakin, Mahone, & Jacobson, 2015). The DAS-II Pattern Construction and Copying, and NEPSY Visual Attention tasks also involve motor speed and one previous study did find evidence for slower motor speed in girls with ADHD who also had high SCT (Hinshaw et al, 2002); the current study also showed higher teacher rated SCT symptoms predicted slower simple reaction times in the computerized Bubbles task, and poorer inhibition on the Animal Go/NoGo task.…”
Section: Discussionmentioning
confidence: 99%
“…Although these two child studies demonstrated modest associations between SCT and sleep (Becker et al, 2015c, Koriakin et al, 2015), several methodological considerations should be noted. First, both studies relied on single-item, non-validated measures of sleep.…”
Section: Introductionmentioning
confidence: 91%
“…In a sample of 746 children referred for neuropsychological assessment, Koriakin et al (2015) found that parent ratings of their child’s sleep problems (i.e., difficulty falling asleep, difficulty waking, restless sleep) were significantly correlated with parent-rated SCT symptoms. However, the magnitude of the correlations was modest ( r s = .12-.24), and only difficulty waking remained significantly associated with greater SCT symptoms when controlling for ADHD and internalizing symptoms (Koriakin et al, 2015). Similarly, Becker and colleagues (2015c) found that SCT was only modestly associated with sleep functioning in a sample of 147 children diagnosed with ADHD Predominantly Inattentive Type.…”
Section: Introductionmentioning
confidence: 99%
“…Toward this end, although a standard symptom set for assessing SCT is itself an important goal, it may be easier for investigators to freely examine its measurement -both at the construct level and at the individual symptom level. There may also be separate dimensions within SCT that are important to examine in terms of etiology, course, and associations with impairment and treatment response [27,40,[100][101][102][103][104]. In agreement with Lahey and colleagues [23], the overarching SCT construct may be too large a "grain size" for understanding its psychobiology since it includes a range of cognitive, psychomotor, and motivational components while at the same time the SCT construct may be too small if not examined and understood within higher-order models of psychopathology.…”
Section: Key Considerations For Examining Sct Within Hierarchical Modmentioning
confidence: 99%